Transitions in Interface Objects: Searching Databases. (23rd May 2016) - Gamble, Tim; May, Jon
Abstract : Two experiments demonstrate that a list-like database interface which benefits from the persistence of contextual information does not show the same degree of benefit of collocating objects over display changes that has been previously observed in a map-searching study. This provides some support for the claim that the nature of the task must be taken into account in choosing how to design dynamic displays. We discuss the benefit of basing design principles on theoretical models derived from film cutting methods used in cinematography, so that they can be extended to novel design situations.